Is there any correlation among MKK4 (mitogen-activated protein kinase kinase 4) expression, clinicopathological features, and KRAS/NRAS mutation in colorectal cancer. (2nd August 2020) - Dogan, Mutlu; Guresci, Servet; Acikgoz, Yusuf; Ergun, Yakup; Kos, Fahriye Tugba; Bozdogan, Onder; Bal, Oznur
ABSTRACT: Background: We aimed to evaluate the correlation between MKK4 expression and clinicopathological features, KRAS/NRAS mutation in colorectal cancer. Methods: MKK4 expression was assessed by immunoreactivity score (IRS). Staining intensity(SI) and percentage of positively stained cells (PP) were used for IRS (IRS = SI×PP). Cutoffs were explored with ROC analysis. Patients were grouped as WIR ('weak immunoreactive'; IRS:0–2) and SIR ('strong immunoreactive'; IRS: >3). Results: We enrolled 95 patients. 63.2% had metastasis. Median follow-up was 31.4 months. KRAS/NRAS mutation rate was 45.2%. Median values for OS, DFS, and PFS were as 31.6, 17.2, and 10.3 months. WIR group had longer OS ( p = 0.03). Recurrence rate was 36.8%. Median DFS was longer for recurrent patients in WIR group ( p = 0.055). KRAS or NRAS wild-type patients and those with left-sided tumors in WIR group had longer OS ( p = 0.029, p = 0.024, p = 0.03). There was no PFS difference ( p : 0.15). In correlation analysis, there was a negative correlation between MKK4 expression and KRAS mutation, NRAS mutation, OS, PFS, DFS ( r : –0, 06; r : –0, 02; r : –0, 10; r : –0, 06; r : –0, 34). Only the correlation for MKK4 expression and DFS was significant ( p = 0.04). Conclusion: MKK4 expression inversely correlates with survival outcomes. Patients with KRAS/NRAS wild-type, left-sided tumors with WIR had longer OS.